Urgensi Revisi Peraturan Pemerintah Pengganti Undang-Undang Nomor 23 Tahun 1959 Sebagai Kontekstualisasi Iklim Demokrasi - Ahmad Gelora Mahardika (Justitia Jurnal Hukum, 2020)
Article 12 of the 1945 Constitution of the Republic of Indonesia states that the President has the authority to determine state of emergency, meanwhile the emergency requirements are determined by law. In the Indonesian legal system, the only regulation issued in emergency situation is in lieu of law Number 23 of 1959. The lieu of law was issued by the President in an unstable condition, namely a change of the constitution from the 1950 Constitution to the 1945 Constitution. testing by the House of Representatives, whereas the testing of the lieu of law is a requirement determined in Article 22 of the 1945 Constitution. In addition to these factors, in lieu of law No. 23 of 1959 is also material which is often opposed to democratic values. Therefore, revision of in lieu of law Number 23 of 1959 is needed, because in lieu of law Number 23 of 1959 has not fulfilled the requirements in accordance with the current requirements. The research method used in this article is normative juridical. The conclusion in this article is in lieu of law No. 23 of 1959 needs to be immediately revised as a contextualist welfare of democracy.